2021
DOI: 10.3390/jpm11020154
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Profiling of Genomic and Transcriptomic Differences between Risk Groups of Lung Adenocarcinoma and Lung Squamous Cell Carcinoma

Abstract: Lung cancer is the second most frequently diagnosed cancer type and responsible for the highest number of cancer deaths worldwide. Lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) are subtypes of non-small-cell lung cancer which has the highest frequency of lung cancer cases. We aimed to analyze genomic and transcriptomic variations including simple nucleotide variations (SNVs), copy number variations (CNVs) and differential expressed genes (DEGs) in order to find key genes and pathways for d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 117 publications
0
18
0
Order By: Relevance
“…Gene mutation, including copy number variation (CNVs) and single-nucleotide polymorphism (SNPs), plays important roles in the development and progression of human cancers [ 44 , 45 ]. However, the effect of CNV and SNP in m6A-related genes remain unknown to us.…”
Section: Discussionmentioning
confidence: 99%
“…Gene mutation, including copy number variation (CNVs) and single-nucleotide polymorphism (SNPs), plays important roles in the development and progression of human cancers [ 44 , 45 ]. However, the effect of CNV and SNP in m6A-related genes remain unknown to us.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MGA was found to mutate frequently in multiple types of cancers, thus providing a novel insight into the function of MGA ( De Paoli et al, 2013 ; Cancer Genome, Atlas Research, and Network, 2014 ; Jo et al, 2016 ; Zhang et al, 2018 ). Zengin and Önal-Süzek (2021) reported that MGA was a driver gene in LUAD but not in LUSC. Nonetheless, the specific role of MGA mutation in cancer is unclear, and the role of MGA mutation in ICI treatment outcome was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…Although addition of the top 10 most highly mutated somatic driver genes to the classification model did not improve the performance of LUAD patients, they vastly improved the classification model of LUSC patients (Table 8). Top 10 somatically mutated genes of LUSC patients reported in our previous publication were CDKN2A, CSMD3, FAT1, KEAP1, KMT2C, KMT2D, NF1 NFE2L2, PIK3CA, TP53 [16]. The correlation between the risk of the patient (high vs low) and the given ten genes, the CSMD3 gene, impacted the model most by improving both the Logistic Regression and Random Forest performance in LUSC (Figure 12 and Figure 13).…”
Section: Somatically Mutated Genesmentioning
confidence: 95%